2021
DOI: 10.1155/2021/1386078
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Improves Mitochondrial Function and Inflammation in H2O2-Induced Oxidative Stress Damage in the Gastric Mucosal Epithelial Cell by Regulating the PI3K/AKT Signaling Pathway

Abstract: Functional dyspepsia (FD) is one of the most common functional gastrointestinal disorders, the therapeutic strategy of which it is limited due to its complex pathogenesis. Oxidative stress-induced damage in gastric mucosal epithelial cells is related to the pathogenesis and development of FD. Quercetin (Que) is one of the active ingredients of Zhishi that showed antioxidant, antiapoptotic, and anti-inflammatory effects. The aim of this study is to investigate the effect of Que on oxidative stress-induced gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
3
6
0
Order By: Relevance
“…In the current experiment, consistent with improved intestinal barrier function, PCA and Que rescued the protein expression and distribution of occludin, claudin-1 and ZO-1 as measured by confocal microscopy. In accordance with our study, PCA and Que have been reported to improve protein expression of occludin, claudin-1 and ZO-1 in vivo and vitro [ 42 – 44 ]. In our present study, it is possible that PCA and Que may partially protect intestinal barrier function via improving protein expression and rescuing distribution of intestinal tight junctions.…”
Section: Discussionsupporting
confidence: 91%
“…In the current experiment, consistent with improved intestinal barrier function, PCA and Que rescued the protein expression and distribution of occludin, claudin-1 and ZO-1 as measured by confocal microscopy. In accordance with our study, PCA and Que have been reported to improve protein expression of occludin, claudin-1 and ZO-1 in vivo and vitro [ 42 – 44 ]. In our present study, it is possible that PCA and Que may partially protect intestinal barrier function via improving protein expression and rescuing distribution of intestinal tight junctions.…”
Section: Discussionsupporting
confidence: 91%
“…In the current experiment, consistent with improved intestinal barrier function, PCA and Que rescued the protein expression and distribution of occludin, claudin-1 and ZO-1 as measured by confocal microscopy. In accordance with our study, PCA and Que have been reported to improve protein expression of occludin, claudin-1 and ZO-1 in vivo and vitro [34][35][36]. In our present study, it is possible that PCA and Que may partially protect intestinal barrier function via improving protein expression and rescuing distribution of intestinal tight junctions.…”
Section: Discussionsupporting
confidence: 91%
“…Synthesis of cDNA by reverse transcription was performed, and then the cDNA was analyzed by SYBR Premix Ex TaqII (Takara, RR820A). The level of the target gene was calculated by 2 −△△Ct method [ 30 ], and GAPDH was used as the internal reference. The gene primer sequences are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%